Using Ecotech Architecture as an Effective Tool for Sustainability in Construction Industry - Mozhdegani, A. S.; Afhami, R. (Engineering, Technology & Applied Science Research, 2017)
Ecotech architecture can be used as an effective strategy to minimize energy consumption and enhance the satisfaction of construction industry beneficiaries in the Middle East. The use of ecotech principles has been employed in different parts of the world. However, following a universal approach is not possible as local conditions are always to be considered Applications and examples of ecotech architecture are investigated in this paper. A proposed building design for the Cheetgar region in Tehran is also briefly demonstrated. A further insight on Masdar city in Abhu Dabi is provided. An overall discussion is made and key conclusions are drawn.